Epidemiology of cervical cancer in Kelantan - Hussin, Mohd Ariff; Ismail, Aziz asSafi; Othman, Shukri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Cancer of the cervix is one of the most serious illnesses affecting women today - particularly in developing countries. It is the fifth common cancer worldwide and is second only to breast cancer as the leading cause of deaths in women. Half a million cases are diagnosed annually with the highest rates occurring in developing countries (Crook T and Farthing A.,l993). In the South as well as in Central America; sub-Saharan Africa; south and as well a south-east Asia; it is the most or second most common cancer among women (Walboomers J1vnvf et a/.,1999). In Malaysia, a figure of 2191 new cases of cancer of the cervix was reported in 1993 (Ministry of Health, 2002). The most common ~ancer in women was breast cancers, cervical cancers, colon, ovarian, and leukemia's. However, the actual number of cases could be expected to be more in view of the fact that notification of cases is notoriously inaccurate in the Malaysian context. The vast majority of cervical cancer cases are caused by infection with certain subtypes of human papilloma virus (HPV), a sexually transmitted virus that infects cells and may result in precancerous lesions ~and invasive cancer (Walboomers JMM et a!., 1999). Developing countries accounted for 370 000 out of the total 466 000 cases of cervical cancer estimated to occur in the world in the year 2000 (Ferley J. et a/.,2000). Worldwide, cervical cancer claims the lives of 231 000 women annually, over 80 % of whom lived in developing countries. Key risk factors to the cancer of the cervix in some countries have been investigated extensively. Potentially strong cofactors have been identified as smoking, oral contraceptive use, parity and interaction with other sexually transmitted viruses (Larsen NS, 1994). Sexual practices (e.g. age at first coitus, number of sexual partners) (Brinton LA et al., 1987) and male factors ( eg circumcision, occupation ) have been incriminated too in increasing the risk of developing cancer of the cervix.Cancer of the cervix is found mainly to occur in older women, especially those between 40 and 50 years of age. There is, however, a new trend evolving whereby younger women are found to be developing the disease (Azhar MT.,l994) This may be due to changing sexual norms and physico-psychological developments (e.g. earlier age at menarche, widespread availability of contraceptives, sexual liberation etc). Cancer of the cervix is the one type of cancer for which a lmown and effective preventive strategy exists. The natural history of the disease, with its precursor state or 'dysplasia' and in-situ changes, as well as the anatomic availability and easy access of the cervix for repeated examination, are call circumstances particularly suited to a screening programme (CMA Journal, 1976). Added to this is the fact that many of the risk factors for cancer of the cervix is related to sexual practice, an intimate and highly confidential aspect of a person's life, as well as her socioeconomic status. These two aspects of life are known to be difficult to penetrate, perpetrate and modify, hence health promotion strategies are not cost effective. Hence, early detection of disease via screening measures is the logical solution. The Papanicolaou (Pap) smear remains the most effective screening tool for this cancer. It has been found to reduce the incidence of cancer of the cervix in many areas of the world (Miller AB., 1992). The risk of developing cancer of the cervix is three times higher in unscreened women as compared to those screened for the disease (Herrero R. et al., 1992). However, problems abound with the use of the Pap smear, chiefly those dealing with technical and interpretational aspects. Other methods of screening are also being evaluated for suitability and cost effectiveness. These include cervico-graphy and 'down-staging' a WHO propagated method of screening. In Malaysia at the present moment, there is no existing nationwide screening programme for cancer of the cervix. Opportunistic screening and time to time campaigns are being done on a relatively modest scale (with low yields) using the Pap smear screening method done by the Ministry . of Health (Maternal and Child Health services), the NationalPopulation and Family Development Board as well as the private sector. As in the case of many countries, there is under-utilization of available screening services and low uptake of screening especially among those women at high risk.